Confirmatory Factor Analysis of Perceived Educational Effectiveness Scale for Teachers of Students with Hearing Impairment - Zafar, Saira; Fazil, Hina (Annals of Human and Social Sciences, 2022)
The goal of this study was to create an indigenous scale that would assess the perception of the teachers of students with hearing impairment about the educational effectiveness in Government special education institutions in Punjab Province as well as the psychometric properties of their perceptions of the educational effectiveness. This study applied a quantitative perspective to approach the problem. The population of this study included teachers of pupils with hearing impairment who were working in government special education institutions in Punjab Province. The sample for this study was chosen using a random sampling strategy. As a sample for this study, 300 teachers of students with hearing impairments were chosen. The researchers created an indigenous scale. 50 statements were all scored out of five point likert scale. Confirmatory factor analysis was carried out through IBM SPSS AMOS (Analysis of moment structure) version 25.0 using structural equation modeling (SEM).